2016
DOI: 10.1111/pbi.12662
|View full text |Cite
|
Sign up to set email alerts
|

Tomato facultative parthenocarpy results from SlAGAMOUSLIKE6loss of function

Abstract: SummaryThe extreme sensitivity of the microsporogenesis process to moderately high or low temperatures is a major hindrance for tomato (Solanum lycopersicum) sexual reproduction and hence year‐round cropping. Consequently, breeding for parthenocarpy, namely, fertilization‐independent fruit set, is considered a valuable goal especially for maintaining sustainable agriculture in the face of global warming. A mutant capable of setting high‐quality seedless (parthenocarpic) fruit was found following a screen of EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(155 citation statements)
references
References 72 publications
3
148
0
4
Order By: Relevance
“…Taking an even more sophisticated approach in tomato, Rodríguez‐Leal et al () demonstrated that a whole range of variability in locule number and fruit size can be obtained by producing an array of CLV3 promoter variants with different fragment deletions. Cas9‐mediated knockout of AGL6 caused facultative parthenocarpy in tomato, which results in seedless fruits (Klap et al ). Reduced seed shattering was achieved by knocking out the ALCATRAZ gene of rapeseed (Braatz et al ).…”
Section: Applications Of Targeted Genome Modification By Nhejmentioning
confidence: 99%
“…Taking an even more sophisticated approach in tomato, Rodríguez‐Leal et al () demonstrated that a whole range of variability in locule number and fruit size can be obtained by producing an array of CLV3 promoter variants with different fragment deletions. Cas9‐mediated knockout of AGL6 caused facultative parthenocarpy in tomato, which results in seedless fruits (Klap et al ). Reduced seed shattering was achieved by knocking out the ALCATRAZ gene of rapeseed (Braatz et al ).…”
Section: Applications Of Targeted Genome Modification By Nhejmentioning
confidence: 99%
“…Regarding MBS, because of the comparatively low number of EMS‐induced SNPs, reducing the candidate genetic variants to few SNPs or possibly to a single SNP when present in a highly recombigenic region, can be straightforward. Reported sizes for MBS‐mapped traits are typically in the 1–4 Mb range and the number of candidate mutations is <10, as indicated for the fruit color mutant psy1, cutin deficient mutant gpat6‐a and fruit parthenocarpy mutation in SlAGL6 gene (Garcia et al ., ; Petit et al ., ; Klap et al ., ). Recombinant analysis is then usually performed to unequivocally identify the causal mutation (Figure ).…”
Section: Accelerating Trait Discovery In Tomato Using Deep Sequencingmentioning
confidence: 97%
“…In contrast, to date, only two advanced studies in tomato have been described: precise targeting of the pectate lyase ( PL ) gene, which resulted in delayed fruit softening without perturbing other ripening-related parameters (Uluisik et al, 2016); and editing the SlAGAMOUS-LIKE 6 ( SlAGL6 ), a MADS-box transcription factor which provides tolerance to heat stress conditions and results in parthenocarpic fruits (Klap et al, 2016). …”
Section: New Plant Breeding Techniques (Npbt) For Fruit Quality Studiesmentioning
confidence: 99%